2013
DOI: 10.3791/50340
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Cystography

Abstract: Conventional pediatric cystography, which is based on diagnostic X-ray using a radio-opaque dye, suffers from the use of harmful ionizing radiation. The risk of bladder cancers in children due to radiation exposure is more significant than many other cancers. Here we demonstrate the feasibility of nonionizing and noninvasive photoacoustic (PA) imaging of urinary bladders, referred to as photoacoustic cystography (PAC), using near-infrared (NIR) optical absorbents (i.e. methylene blue, plasmonic gold nanostruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Jeon et al demonstrated the feasibility of photoacoustic cystography by NIR dyes with low toxicity. 101 Thus, appropriate multimodal molecular probes can exert synergistic advantages over any single modality alone.…”
Section: Multimodal Nirf Probesmentioning
confidence: 99%
“…Jeon et al demonstrated the feasibility of photoacoustic cystography by NIR dyes with low toxicity. 101 Thus, appropriate multimodal molecular probes can exert synergistic advantages over any single modality alone.…”
Section: Multimodal Nirf Probesmentioning
confidence: 99%
“…imaging, urinary bladder imaging, imaging of neoangiogenesis, GIT imaging, etc. [33][34][35][36][37][38][39][40][41][42].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%